Synthesis of New 1,1,3,3-Tetra(4?-oxy-3-substituted-chalcone)-5,5-diphenylcyclotriphosphazene Derivatives and Investigation of Their Anti Cancer Activities - Tekin, S.; Tekin, I.; Koran, K.; Gorgulu, A. O.; Sandal, S. (Wiley, 2017)
[Abstract Not Available]